(3ahGFO CHj TYjH YHO Gddg Hf GdMSf Hf CMeO GdMQGfis - (3CHh GdMSf CMeO Hf eMeO Hf CMeO GdRYaQGfjs ((3eSYhO Hf CMeO Hf eSYhO GdMGQKi s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe QVi GdOjf CHh HcQ Hf YeQ Hf Ydi GdbSfWjfi Yf GdfHi Udi Gddg Ydjg hSde bGd (B: (3CYWjH NeSkG de jYWgfi CMO bHdi GdMOjK s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3Gddge HGQc dCeJi ai HchQgG BNQ GdLRA s
(3GdfSNI HgG MhGTs
(3QhGjI Yf CHh eMeO YHO GdYRjR Hf CMeO Hf GdNWGH GdQRGRs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3eLGejY (B124) s
Keywords: (3GdMOjK h GdeUWdMs